As desdobras da morte em “A desumanização”, de Valter Hugo Mãe : entre espelhos e narrativas - Guimarães, Thiago Maciel (2016)
In this work, we learn an analysis about some consequences from the death in the novel A desumanização, which was written by Valter Hugo Mãe, a Portuguese writer. Having as a guide the principles of phenomenological-hermeneutical method, we seek a concatenation between some themes of history, literary theory, psychoanalysis and philosophy. The death in his power biases (Aristotle, 2002) and happening (Deleuze, 2012; ECO, 1989) also permeated the analysis. In this way, emphasizing the contemporary and also we located historically some of the meanings and metaphorical levels of death that were manifested in the novel. Therefore, we explore, at first, the aspects of death as a universal power over life. Then we restrict ourselves to the death of Sigridur and to the metaphorical slips of this event on the existence of Halla, her twin sister and also narrator, both characters in the novel. This link has been explained from the intricate relationship of similarities among the twins and the symbolic knots arising from it. Still on that path, we focus on functions relating to the mirrors in different dimensions that appear in the work, in order to expand the understanding of this seemingly inseparable connection. Thus, our reading pursues the paths of (un)folds, based on Deleuze (2012), to deal with this challenging double panorama. We continue the analysis dedicating ourselves to understand how a traumatic situation can be reflected in the language of the subjects, especially in what concerns the silences and the prohibitions arising from culture and its socio-historical setting. Finally, we try to explain the narrative function in the novel, like an assembly capable of modeling places and (un)do differences. To do so, we discuss issues relating to the position of the subject in producing its narrative regarding the inflection and the point of view. We did this while implying the role of resistance and also of support arising from multiple spaces that make up the social order. Thus, this research reflects on the possibilities of death and metaphorical rebirth of Halla.